2023
DOI: 10.3389/fmed.2023.1158768
|View full text |Cite
|
Sign up to set email alerts
|

Targeting intracellular pathways in idiopathic inflammatory myopathies: A narrative review

Abstract: In recent decades, several pieces of evidence have drawn greater attention to the topic of innate immunity, in particular, interferon (IFN) and Interleukin 6 in the pathogenesis of idiopathic inflammatory myopathies (IIM). Both of these molecules transduce their signal through a receptor coupled with Janus kinases (JAK)/signal transducer and activator of transcription proteins (STAT). In this review, we discuss the role of the JAK/STAT pathway in IIM, evaluate a possible therapeutic role for JAK inhibitors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…Type 1 IFN signaling is mediated by the JAK-STAT pathway, whose modulation with the novel JAK-inhibitors has proved efficacious in different autoimmune diseases. Growing evidence indicates that JAK-STAT signaling is also involved in both pro-inflammatory and pro-fibrotic processes in ILD, and JAK-inhibitors are being successfully employed for the treatment of both COVID-19 disease and rapidly-progressive CTD-ILD [86][87][88][89][90]. Recently, a phase II RCT of Filgotinib (a Jak1-inhibitor) in pSS failed to reach its primary endpoint, consisting of a composite outcome measure; however, a sub-analysis of the trial showed a trend toward clinical efficacy in patients with severe disease [91].…”
Section: What Is the Prognosis Of Patients With Pss-ild? How Can We I...mentioning
confidence: 99%
“…Type 1 IFN signaling is mediated by the JAK-STAT pathway, whose modulation with the novel JAK-inhibitors has proved efficacious in different autoimmune diseases. Growing evidence indicates that JAK-STAT signaling is also involved in both pro-inflammatory and pro-fibrotic processes in ILD, and JAK-inhibitors are being successfully employed for the treatment of both COVID-19 disease and rapidly-progressive CTD-ILD [86][87][88][89][90]. Recently, a phase II RCT of Filgotinib (a Jak1-inhibitor) in pSS failed to reach its primary endpoint, consisting of a composite outcome measure; however, a sub-analysis of the trial showed a trend toward clinical efficacy in patients with severe disease [91].…”
Section: What Is the Prognosis Of Patients With Pss-ild? How Can We I...mentioning
confidence: 99%